DIDACTIC CAPABILITIES OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN ENHANCING THE EFFECTIVENESS OF TEACHING THE THEORY OF CURVES IN DIFFERENTIAL GEOMETRY - Kaipnazarova, Guljaxan Xojanazarovna; Kaipnazrova, Damegul Ungarbaevna (SCIENCE and SOCIETY, 2026)
The article analyzes the scientific and methodological foundations of applying a topological approach and modern information and communication technologies (ICT), particularly the GeoGebra software, in teaching the ’Curves’ topic in differential geometry.